Epoxidation of propene in a confined Taylor flow (CTF) reactor at atmospheric pressure - Shin,SB; Lee,D-W; Chadwick,D (CHEMICAL ENGINEERING RESEARCH & DESIGN, 2017)
Heterogeneous catalytic epoxidation of propene to propene oxide with hydrogen peroxide as oxidant was investigated in a confined Taylor flow (CTF) reactor, a continuous monolith reactor, containing a long alumina rod coated with titanium silicalite (TS-1) catalyst in the centre of the reactor column. The effect of gas and liquid superficial velocity on the hydrodynamics of CTF reactor was also investigated under Taylor flow regime at atmospheric pressure. The variation of hydrodynamics had a profound impact on the production of propene oxide. When liquid superficial velocity was constant, the concentration of propene oxide produced decreased with increasing gas superficial velocity as Taylor bubble length and bubble rise velocity increase. However, when gas superficial velocity was constant, the concentration of propene oxide produced had no linear dependency on liquid superficial velocity as Taylor bubble length decreases but bubble rise velocity increases.